THE CHILEAN "NORTE G RANDE": A HISTORICAL DEFINIT ION OF HIS LIMITS, Z ONES AND BORDERLINES, AND THE IMPORTANCE OF CITIES AS GEOSYMBOLS IN BORDERS - González, Sergio (Revista de Historia Social y de las Mentalidades, 2025)
This article analyzes the  historical development of the Big North of Chile during the  19 th century and the first third of the 20 th century, with its own various border areas and  frontier boundaries, where certain geosymbols have had a very relevant role demarcating. However, it con siders the urbanization of the frontier as a key process in the social and  cultural reproduction of the nation - state. It emphasizes in that process of urbanization of the  Big North of Chile, the importance of the Atacama Desert and some cities as geosymbol s, it  analyzes the cases of Antofagasta, Iquique and Arica. It also theoretically discusses the difference between the frontier boundary and  border line, it associates the first concept with problematic issues typical of the 19 th and 20 th centuries, where the frontier is a rigid demarcator of the otherness and, the second concept,  it connects it with the globalization phenomenon and the possibility to build in the  developed frontiers strategic alliances and transbordering associative regions
Keywords: border areas; frontier boundary; border lines; geosymbols; transborder